2002
DOI: 10.1021/cr000031c
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Linkage Isomers of Transition-Metal Nitrosyl Compounds and Related Complexes

Abstract: I. Introduction 883 II. Photocrystallography 883 A. Crystallography of Light-Induced Species 883 B. Supporting Techniques 863 III. Metastable Isomers of Transition-Metal Nitrosyl Complexes 863 A. The First Discoveries 863 B. The Nature of the Metastable States of Sodium Nitroprusside 864 1. Sodium Nitroprusside (SNP): Experimental Methods 864 2. Orbital Ordering of the SNP Ground-State Species 866 3. Theoretical Calculation of the Metastable and Excited States and the Mechanism of Photoinduced Interconversion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
332
2
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 418 publications
(349 citation statements)
references
References 134 publications
13
332
2
2
Order By: Relevance
“…Indeed inorganic photochemistry typically requires the recoordination of solvent or electrolytes, for example, to reverse the process, and the reversal is favored thermodynamically (vide supra). Nevertheless, the photo-and redox-triggered linkage isomerization of nitrosyl (79) and sulfoxyl (80) inorganic complexes demonstrates the potential versatility of inorganic photochemistry. In systems in which a ligand can engage in two alternate coordination modes, such as in the sulfoxide ligand of the complex [Ru II (tpy)(pic)(DMSO)] + (where tpy stands for terpyridine acid and pic for picolinic acid) (Figure 14), the rate of the photo-induced switching is less sensitive to the immediate environment, and the complex can be employed in a similar manner to organic photoswitches.…”
Section: Photoswitching In Polymersmentioning
confidence: 99%
“…Indeed inorganic photochemistry typically requires the recoordination of solvent or electrolytes, for example, to reverse the process, and the reversal is favored thermodynamically (vide supra). Nevertheless, the photo-and redox-triggered linkage isomerization of nitrosyl (79) and sulfoxyl (80) inorganic complexes demonstrates the potential versatility of inorganic photochemistry. In systems in which a ligand can engage in two alternate coordination modes, such as in the sulfoxide ligand of the complex [Ru II (tpy)(pic)(DMSO)] + (where tpy stands for terpyridine acid and pic for picolinic acid) (Figure 14), the rate of the photo-induced switching is less sensitive to the immediate environment, and the complex can be employed in a similar manner to organic photoswitches.…”
Section: Photoswitching In Polymersmentioning
confidence: 99%
“…This is consistent with previous studies that have shown that multiple photons are needed to form iso-S 0 from S 0 and that the formation of iso-S 0 relies upon the presence of a stable, photochemically accessible η 2 -S 0 intermediate. 8,21,22 Since neither species B nor C can be assigned to η 2 -S 0 or iso-S 0 , the unassigned peaks must be due to excited state bent-NO complexes. The calculated NO stretching frequencies for both T 1 (1664 cm -1 ) and Since the calculated NO stretching frequencies of S 1 and T 1 are indistinguishable given the accuracy of DFT calculations, 36 we have used the calculated potentials in Figures 10b and 10c to further differentiate between them.…”
Section: Ground and Lowest Excited State Potential Energy Surfacesmentioning
confidence: 99%
“…charge transfer processes or isomerisation reactions ( [1][2][3][4][5] and references therein). In this manner structures and chemical complexes become accessible which cannot be realized by standard synthetic methods.…”
Section: Introductionmentioning
confidence: 99%
“…In this manner structures and chemical complexes become accessible which cannot be realized by standard synthetic methods. Static neutron diffraction experiments investigating lightinduced structural changes were started on the optically switchable system Na 2 [Fe(CN) 5 NO]2H 2 O (SNP) [6] which is of interest due to its outstanding photorefractive properties [7]. In SNP two metastable linkage-isomers, labelled SI and SII, of the NO-ligand are generated by light irradiation in the blue-green spectral range as illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%